Uganda : Technical Assistance Report-Implementing the Public Financial Management Bill. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses recommendations for implementing the Public Financial Management (PFM) Bill in Uganda. The finalization of the PFM Bill has reached an advanced stage with Parliamentary approval expected in the coming months. The IMF mission strongly recommends that the petroleum revenue management provisions in the Bill are revisited. In particular this should include clearly defining the nature of the funds and its objectives. The reporting arrangements should also be clarified and the specialist audit arrangements specified. Finally, the Bill should be enhanced to ensure that investment risks are limited and to protect against its use as a development fund.